Dietary protein intake and chronic kidney disease. Issue 1 (January 2017) - Ko, Gang Jee; Obi, Yoshitsugu; Tortorici, Amanda R.; Kalantar-Zadeh, Kamyar
Abstract : Purpose of review: High-protein intake may lead to increased intraglomerular pressure and glomerular hyperfiltration. This can cause damage to glomerular structure leading to or aggravating chronic kidney disease (CKD). Hence, a low-protein diet (LPD) of 0.6–0.8 g/kg/day is often recommended for the management of CKD. We reviewed the effect of protein intake on incidence and progression of CKD and the role of LPD in the CKD management. Recent findings: Actual dietary protein consumption in CKD patients remains substantially higher than the recommendations for LPD. Notwithstanding the inconclusive results of the 'Modification of Diet in Renal Disease' (MDRD) study, the largest randomized controlled trial to examine protein restriction in CKD, several prior and subsequent studies and meta-analyses appear to support the role of LPD on retarding progression of CKD and delaying initiation of maintenance dialysis therapy. LPD can also be used to control metabolic derangements in CKD. Supplemented LPD with essential amino acids or their ketoanalogs may be used for incremental transition to dialysis especially on nondialysis days. The LPD management in lieu of dialysis therapy can reduce costs, enhance psychological adaptation, and preserve residual renal function upon transition to dialysis. Adherence and adequate protein and energy intake should be ensured to avoid protein-energy wasting. Summary: A balanced and individualized dietary approach based on LPD should be elaborated with periodic dietitian counseling and surveillance to optimize management of CKD, to assure adequate protein and energy intake, and to avoid or correct protein-energy wasting.